2020
DOI: 10.1021/acs.jmedchem.0c00310
|View full text |Cite
|
Sign up to set email alerts
|

2-Oxaadamant-1-yl Ureas as Soluble Epoxide Hydrolase Inhibitors: In Vivo Evaluation in a Murine Model of Acute Pancreatitis

Abstract: In vivo pharmacological inhibition of soluble epoxide hydrolase (sEH) reduces inflammation and pain, suggesting sEH as a pharmacological target for the treatment of inflammatory diseases, including acute pancreatitis (AP). Adamantyl ureas are very potent sEH inhibitors but the lipophilicity of the adamantane group compromises their overall solubility. Herein, we report that the replacement of a methylene unit of the adamantane group by an oxygen atom increases the solubility of three series of urea-based sEH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…The replacement of adamantyl and 4-(trifluoromethoxy)phenyl groups with natural bicyclic lipophilic groups provided a series of sEHIs with similar potency and 10-fold more water solubility compared to the original compounds [ 82 ]. On a similar note, Codony and coworkers developed 2-oxaadamant-1-yl urea-based molecules and reported that the replacement of a methylene unit of the adamantane group by an oxygen atom increased the solubility, permeability, and stability with nanomolar sEH inhibitory potency [ 83 ]. Pharmacophore-based virtual screening has been used for discovery of 6-amino-2-((4-chlorobenzyl)thio)-5-phenylpyrimidin-4(3H)-one and urea-based potent sEHIs [ 84 ].…”
Section: Soluble Epoxide Hydrolase Inhibitors (Sehis)mentioning
confidence: 99%
“…The replacement of adamantyl and 4-(trifluoromethoxy)phenyl groups with natural bicyclic lipophilic groups provided a series of sEHIs with similar potency and 10-fold more water solubility compared to the original compounds [ 82 ]. On a similar note, Codony and coworkers developed 2-oxaadamant-1-yl urea-based molecules and reported that the replacement of a methylene unit of the adamantane group by an oxygen atom increased the solubility, permeability, and stability with nanomolar sEH inhibitory potency [ 83 ]. Pharmacophore-based virtual screening has been used for discovery of 6-amino-2-((4-chlorobenzyl)thio)-5-phenylpyrimidin-4(3H)-one and urea-based potent sEHIs [ 84 ].…”
Section: Soluble Epoxide Hydrolase Inhibitors (Sehis)mentioning
confidence: 99%
“…Previously, we have shown that less potent inhibitors displayed fluctuations in the interactions between the urea motif and the catalytic residues, shifting the ensemble toward longer distances. 19 All inhibitors share a common scaffold on the RHS of the urea and MD simulations reported a similar behavior in terms of interactions and conformational dynamics in the RHS and central channel regions. The network of hydrogen bonds and π–π stacking interactions is key to retain the inhibitor in the active site.…”
Section: Resultsmentioning
confidence: 81%
“… 25 Previously, we showed that the active site of EHs present high plasticity. 19 , 26 Available X-ray structures of sEH in complex with adamantyl ureas indicate that the adamantane scaffold can occupy both LHS and RHS pockets. 27 In the case of t -AUCB (PDB: 5AM3), the inhibitor is orientated with the benzoic acid group occupying the RHS, while adamantane sits in the LHS (see Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations